2016
DOI: 10.1371/journal.pone.0151432
|View full text |Cite|
|
Sign up to set email alerts
|

Foliar Essential Oil Glands of Eucalyptus Subgenus Eucalyptus (Myrtaceae) Are a Rich Source of Flavonoids and Related Non-Volatile Constituents

Abstract: The sub-dermal secretory cavities (glands) embedded within the leaves of Eucalyptus (Myrtaceae) were once thought to be the exclusive repositories of monoterpene and sesquiterpene oils. Recent research has debunked this theory and shown that abundant non-volatile compounds also occur within foliar glands. In particular, glands of four species in subgenus Eucalyptus contain the biologically active flavanone pinocembrin. Pinocembrin shows great promise as a pharmaceutical and is predominantly plant-sourced, so E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 68 publications
0
30
0
Order By: Relevance
“…Indeed, we observed a threefold increase in dark respiration at temperatures >50°C, and the majority of CO 2 emitted was not labelled (data not shown). Previous studies have shown that respiration rates increase at temperature higher than 40°C in Eucalyptus spp., ( (Goodger, Seneratne, Nicolle, & Woodrow, 2016), and the increase in temperature, shifting isoprenoid equilibrium from liquid to gas phase, becomes the principal environmental driver of their emission (Grote, Monson, & Niinemets, 2013;Harley, 2013). Although isoprene is expected to be synthesized in the mesophyll and not stored in permanent pools (Niinemets, Loreto, & Reichstein, 2004), we cannot discard the idea that an isoprene pool that is stored in glands and is not quickly labelled by 13 C contributes to isoprene emission after volatilization at very high temperatures.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Indeed, we observed a threefold increase in dark respiration at temperatures >50°C, and the majority of CO 2 emitted was not labelled (data not shown). Previous studies have shown that respiration rates increase at temperature higher than 40°C in Eucalyptus spp., ( (Goodger, Seneratne, Nicolle, & Woodrow, 2016), and the increase in temperature, shifting isoprenoid equilibrium from liquid to gas phase, becomes the principal environmental driver of their emission (Grote, Monson, & Niinemets, 2013;Harley, 2013). Although isoprene is expected to be synthesized in the mesophyll and not stored in permanent pools (Niinemets, Loreto, & Reichstein, 2004), we cannot discard the idea that an isoprene pool that is stored in glands and is not quickly labelled by 13 C contributes to isoprene emission after volatilization at very high temperatures.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that respiration rates increase at temperature higher than 40°C in Eucalyptus spp., (Crous, Wallin, Atkin, Uddling, & Ekenstam, ; Way, Holly, Bruhn, Ball, & Atkin, ), with an optimum at about 55°C in Eucalytpus pauciflora (O'Sullivan et al, ). However, Eucalyptus leaves have numerous subdermal secretory cavities (glands) containing terpenes (Goodger, Seneratne, Nicolle, & Woodrow, ), and the increase in temperature, shifting isoprenoid equilibrium from liquid to gas phase, becomes the principal environmental driver of their emission (Grote, Monson, & Niinemets, ; Harley, ). Although isoprene is expected to be synthesized in the mesophyll and not stored in permanent pools (Niinemets, Loreto, & Reichstein, ), we cannot discard the idea that an isoprene pool that is stored in glands and is not quickly labelled by 13 C contributes to isoprene emission after volatilization at very high temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of tea tree and Eucalyptus, terpenes are stored in secretory cavities within the leaf, and their capacity may set a limit to the accumulation of oil in a leaf (King et al, 2004). Goodger & Woodrow (2012) showed that foliar terpene…”
Section: Introductionmentioning
confidence: 99%
“…Feeding rates of animals were significantly depressed by B ring unsubstituted flavanones but not by flavanones with substitutions in the B ring or unsubstituted flavones [9]. Critically, it appears that B ring unsubstituted flavanones only occur in the subgenus Monocalyptus (= Eucalyptus) of the Eucalyptus genus [8,10].…”
mentioning
confidence: 95%